1993
DOI: 10.3109/02841869309083905
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body Autoradiography of123I-Labelled Islet Amyloid Polypeptide (IAPP) Accumulation in the lung parenchyma and in the villi of the intestinal mucosa in rats

Abstract: Islet amyloid polypeptide (IAPP) in a 37 amino-acid pancreatic islet polypeptide, displaying about 50% amino-acid homology with neuropeptide calcitonin gene-related peptide (CGRP). IAPP is co-stored with insulin in the beta-cell secretory granules and co-released with insulin upon stimulation. Human IAPP has the ability to precipitate in the shape of amyloid in patients with type II (non-insulin dependent) diabetes but otherwise its functional or pathophysiological role is enigmatic. In the present study 125I-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The uptake of amylin in lung and intestine was inhibited by administration of unlabeled amylin or CGRP. These results indicated that amylin was bound to receptors in these tissue, and likely exerted biological activity therein 39 . In rats, the intracerebroventricular (1–4 μg) or sc (25–100 μg/kg) administration dose‐dependently inhibited gastric emptying and intestinal transit of charcoal meal 20 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The uptake of amylin in lung and intestine was inhibited by administration of unlabeled amylin or CGRP. These results indicated that amylin was bound to receptors in these tissue, and likely exerted biological activity therein 39 . In rats, the intracerebroventricular (1–4 μg) or sc (25–100 μg/kg) administration dose‐dependently inhibited gastric emptying and intestinal transit of charcoal meal 20 .…”
Section: Discussionmentioning
confidence: 95%
“…Like CGRP, it is also expressed in many tissues in addition to the stomach and intestines, which include the lungs, peripheral nervous system, and the brain 20 . The iv injection of amylin radiolabeled with 125 I resulted in high levels of radioactivity in the lung parenchyma and in the villi of the small intestinal mucosa, and elevated levels in kidney cortical tissue, whereas radioactivity was low and remained similar to blood levels in other tissue 39 . The uptake of amylin in lung and intestine was inhibited by administration of unlabeled amylin or CGRP.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to CGRP receptors, amylin receptors are heterodimeric complex of calcitonin receptor (CTR) and receptor activity modifying proteins (RAMP) (Christopoulos et al, 1999). High affinity amylin binding sites are located in many regions of the rat and monkey brains; including the hypothalamus, nucleus accumbens, dorsal raphe and area postrema (Stridsberg et al, 1993; Sexton et al, 1994; Paxinos et al, 2004). Little is known relative to the function of amylin in the mammalian nervous system.…”
Section: Introductionmentioning
confidence: 99%